VD_FINDINFO Jug / 2022 / 439 vom 16. November 2021 - VD Tribunal cantonal (2021)
EXCÈS DE VITESSE, LOI FÉDÉRALE SUR LA CIRCULATION ROUTIÈRE, PEINE PRIVATIVE DE LIBERTÉ | 41 al. 1 CP, 42 al. 1 CP, 47 CP, 90 al. 2 LCR